2016
DOI: 10.1111/1756-185x.12791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fetuin‐A and transforming growth factor beta 1 levels in patients with spondyloarthropathies and rheumatoid arthritis

Abstract: We conclude that Fetuin-A may be one of the steps that can be active in disease progression in axial SpA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…A recent study conducted in RA patients showed a non-significant increase in this molecule in the serum of patients compared to healthy controls [39], however our study is the first to evaluate levels of TGFβ1 in the early RA phase. We showed a significant increase in TGFβ1 that may have a compensatory effect in response to increased inflammatory state.…”
Section: Resultsmentioning
confidence: 80%
“…A recent study conducted in RA patients showed a non-significant increase in this molecule in the serum of patients compared to healthy controls [39], however our study is the first to evaluate levels of TGFβ1 in the early RA phase. We showed a significant increase in TGFβ1 that may have a compensatory effect in response to increased inflammatory state.…”
Section: Resultsmentioning
confidence: 80%
“…Кроме того, в своей работе они указали на отсутствие взаимосвязи между уровнем ФА и наличием аортальной кальцификации, связав последнюю с кумулятивной дозой ГК. Имеются единичные работы, в которых взаимосвязь между уровнем ФА и показателями активности РА обнаружена не была, что указывает на необходимость дальнейшего изучения данного вопроса [17,18]. Также следует отметить, что средний уровень ФА в группе условно здоровых лиц различался в данных исследованиях.…”
Section: Discussionunclassified
“…Так, в исследовании S. Ozturk и соавт. [13] Описана взаимосвязь уровня ФА c кумулятивной дозой ГК, но не со степенью активности РА [17,18]. В нашем исследовании 86 (78%) пациентов получали ГК в анамнезе, с медианой кумулятивной дозы -5760 [1900; 13 500] мг.…”
Section: Discussionunclassified
“…Higher levels of this adipokine also correlate with inhibitory actions against adiponectin effects. Inflammation may also be driven by fetuin-A since it can activate TLR-4 and mimic the TGF-β receptor [ 118 , 119 , 147 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%